Market Response to the Launch of Indonesia’s Sovereign Wealth Fund - Siska, Elmira; Aryal, Narayan Prasad; Singh, Gobind Kumar; Indra, Natal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to investigate the short-term impact of Danantara’s launch, a newly established sovereign wealth fund in Indonesia, on market performance. A quantitative research design is employed in this study with an event study approach. The observed variables are stock returns and trading volume during 15 trading days before the launch of Danantara and 15 trading days after the launch of Danantara. Data were obtained from the IDX report. Paired-sample t-tests were conducted to identify any significant differences in Jakarta Composite Index (JCI) returns and trading volume. The results show no statistically significant changes in either variable, indicating that the market may have already priced in the policy or remained cautious due to limited information regarding the fund’s governance and implementation. Theoretically, these findings suggest that policy announcements do not necessarily trigger immediate market reactions when clarity is lacking. Practically, the study highlights the importance of transparent governance structures and effective communication in shaping investor sentiment. Future research could extend the observation period to capture delayed market responses and incorporate additional variables for a more comprehensive understanding of Danantara’s long-term effects.